Instructional Digital Leadership for Strengthening Technology-Supported Character Learning through School Partnerships in Elementary Schools - Widyanuar, Yusie; Rahmawati, Tina (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Instructional digital leadership has become increasingly important in fostering technology-supported learning environments that strengthen character education through collaborative school partnerships. However, existing studies remain fragmented in explaining how school principals integrate digital leadership practices with school–family–community partnerships to sustain character learning in elementary schools. This study aims to synthesize the current body of knowledge on instructional digital leadership and its contribution to strengthening technology-supported character learning through school partnerships. A Systematic Literature Review (SLR) combined with bibliometric analysis was conducted following the PRISMA framework. An initial search across Scopus, Web of Science, and Google Scholar identified 2,185 records, from which 29 eligible studies were selected through a rigorous screening and eligibility process. Bibliometric analysis using VOSviewer was employed to map publication trends, authorship networks, geographical distribution, and keyword co-occurrence, while thematic synthesis was used to identify recurring patterns across the selected studies. The findings indicate a growing global interest in integrating instructional leadership, digital technologies, character education, and school partnerships over the past decade. School principals emerge as instructional digital leaders who facilitate technology-supported communication, digital monitoring systems, collaborative professional learning, and innovative learning environments that reinforce character development. The review also highlights six interrelated dimensions of effective instructional digital leadership: reflective practice, positive school culture, institutional support, technology integration, character learning implementation, and professional collaboration. These findings contribute to the advancement of technology-enhanced educational leadership by providing an integrated conceptual perspective that informs future research, educational policy, and leadership practices for sustainable character learning in elementary schools.